Modelagem hidrológica da bacia de contribuição da confluência dos rios Itapetininga e Paranapanema - Galvão, Pedro Ramos (Universidade Federal de São Carlos, 2025)
In the current context of climate change, maintaining existing development patterns would increase the exposure and vulnerability of ecosystems and populations to climate threats. Even if global warming is limited to 1.5 °C, historical extreme events will continue to occur. In Brazil, floods have already caused economic losses exceeding R$70 billion and 644 deaths between 1991 and 2023, highlighting the need to improve water management tools. In this context, hydrological modeling stands out as an essential strategy for disaster prediction and mitigation, though its effectiveness relies on reproducing complex patterns in river basins, particularly during climate extremes. This study applied the HEC-HMS model to the contributing basin of the confluence of the Itapetininga and Paranapanema rivers, a region historically impacted by floods, to evaluate its ability to adequately predict flows for this basin. Methods such as the SCS Curve Number for Loss, SCS Unit Hydrograph for Transform, Muskingum for Routing and Constant Monthly for Baseflow were adopted. The model was calibrated using the extreme precipitation event of 2004, and the obtained parameters were applied to simulate events from 2005, 2011, 2016, and 2017. At the outlet, calibration for 2004 resulted in a NSE of 0.700 and an R² of 0.84, reproducing general runoff patterns. However, in subsequent years, NSE values were negative or near zero, and R² values were mostly close to zero. The analysis revealed the basin’s complexity, marked by heterogeneity and dynamic interactions between fluvial systems and adjacent areas. The results underscore the inherent challenges of hydrological modeling, particularly in climate extremes, and emphasize the need for methodological refinements. Despite limitations, the study highlights opportunities for innovations capable of transforming risk mitigation strategies and strengthening resilience to climate change.
Hydrological modeling of the Itapetininga and Paranapanema rivers confluence watershed
Keywords: Alto Paranapanema; HEC-HMS; Previsão de enchentes; Gerenciamento de risco; Gestão de recursos hídricos; Campina do Monte Alegre; Flood prediction; Risk management; Water resource management; ENGENHARIAS::ENGENHARIA CIVIL::ENGENHARIA HIDRAULICA::HIDROLOGIA